Mecca Treaty of 1926 and its impact on politics The Saudi Foreign Ministry towards Asir (Journal of the College of Basic Education, 2022)
The Arabian Peninsula region received the attention of the major countries in the Middle East during the war. The world's first, being the node of land, sea and air communications between Europe and the Far East. In addition to the international competition in its southwest for control of the coast overlooking the Red Sea.Contemporary historical studies have tended to study the history of the Arabian Peninsula, depending on The method of uncovering British and Ottoman documents and trying to reach historical analyzes and conclusions